A common environmental pollutant, 4‐nonylphenol, promotes allergic lung inflammation in a murine model of asthma. Issue 6 (29th April 2013) - Suen, J. L.; Hsu, S. H.; Hung, C. H.; Chao, Y. S.; Lee, C. L.; Lin, C. Y.; Weng, T. H.; Yu, H. S.; Huang, S. K.
Abstract Background Exposure to environmental hormones, such as alkylphenols, has been suggested to be associated with the development of asthma, but the mechanism of action remains unclear. Objective This study examined the effect of 4‐nonylphenol (NP), one of the most important alkylphenols, on conventional dendritic cells (cDCs) and adaptive T‐cell responses. It also explored the role of aryl hydrocarbon receptor (AhR) in NP's effect. Methods NP‐conditioned bone marrow‐derived DCs (BM‐DCs) and splenic CD11c+ cDCs were assessed regarding function in a murine model under conditions relevant to route and level of exposure in humans. Results Our results showed that splenic cDCs from NP‐exposed mice have potent Th2‐skewing ability and secrete increased levels of IL‐6 and TNF‐α, but not IL‐10 and IL‐12, at baseline and after stimulation with LPS. Further, bone marrow‐derived DCs were cultured in the presence of NP and showed similar cytokine pattern and influenced the antigen‐specific T cells secreting significantly less IFN‐γ. Importantly, NP‐exposed mice developed more severe OVA‐induced allergic lung inflammation compared with control group. Interestingly, in a congenic strain of mice carrying low‐affinity, ligand‐binding mutant AhR (AhRd), NP's effect on DC functions and lung inflammation was not observed in vitro and in vivo. Conclusion These results suggested that NP may disturb physiologic function of DCs through, in part, AhR‐dependent mechanisms, supporting the importance of NP exposure on the regulation of DC functions and allergic inflammation.